Experimental Investigation of 14C in the Primary Coolant of the 10 MW High Temperature Gas-Cooled Reactor. Issue 3 (29th April 2019) - Xie, F; Peng, W; Cao, J; Feng, X; Wei, L; Tong, J; Li, F; Sun, K
ABSTRACT: The very high temperature reactor (VHTR) is a development of the high-temperature gas-cooled reactors (HTGRs) and one of the six proposed Generation IV reactor concept candidates. The 10 MW high temperature gas-cooled reactor (HTR-10) is the first pebble-bed gas-cooled test reactor in China. A sampling system for the measurement of carbon-14 ( 14 C) was established in the helium purification system of the HTR-10 primary loop, which could sample 14 C from the coolant at three locations. The results showed that activity concentration of 14 C in the HTR-10 primary coolant was 1.2(1) × 10 2 Bq/m 3 (STP). The production mechanisms, distribution characteristics, reduction routes, and release types of 14 C in HTR-10 were analyzed and discussed. A theoretical model was built to calculate the amount of 14 C in the core of HTR-10 and its concentration in the primary coolant. The activation reaction of 13 C has been identified to be the dominant 14 C source in the core, whereas in the primary coolant, it is the activation of 14 N. These results can supplement important information for the source term analysis of 14 C in HTR-10 and promote the study of 14 C in HTGRs.